Associations between food insecurity and child and parental physical, nutritional, psychosocial and economic well‐being globally during the first 1000 days: A scoping review - Francesca Rosen; Lily Settel; Faith Irvine; Elizabeth P. D. Koselka; Joshua D. Miller; Sera L. Young (Wiley, 2024)
Abstract Food insecurity affects billions of individuals annually and contributes to myriad poor health outcomes. Experiences of food insecurity may be particularly harmful during the first 1000 days, but literature on the topic has not been synthesized. We therefore aimed to characterize all available studies examining associations between food insecurity and nutritional, psychosocial, physical and economic well‐being among parents and children during this period. We implemented a standardized search strategy across 11 databases. Four researchers screened 10,257 articles, 120 of which met the inclusion criteria. Most studies were conducted in Sub‐Saharan Africa (43.3%), followed by North America (20.8%). Studies were primarily quantitative (95.8%), cross‐sectional (70.0%) and focused on women (pregnant or post‐partum, 48.3%) or women and children (15.8%). Physical health outcomes were the most investigated (n = 87 studies), followed by nutritional (n = 69), psychosocial (n = 35) and economic well‐being (n = 2). The most studied associations were between food insecurity and stunting (n = 15), maternal depression (n = 12), child dietary diversity (n = 7) and maternal body mass index (n = 6). The strength of evidence for the observed associations varied across populations as well as within and between examined outcomes. We recommend that future studies recruit more diverse study populations, consider temporality of relationships, use instruments that facilitate cross‐site comparisons, measure individual‐level food insecurity and outcomes most likely to be impacted by food insecurity, evaluate contextual factors that may modify the effects of food insecurity and employ analytic techniques that permit assessment of causal pathways.